Indigenous Community Participation in Ecotourism Development: The Case of Bukit Tigapuluh National Park - Musadad Musadad; Mariaty Ibrahim; Chelsy Yesicha (Universitas Pendidikan Ganesha, 2022)
Previous studies have explored community participation in ecotourism. However, only a few have addressed indigenous people concerning their participation in ecotourism development, specifically within the context of a national park. Therefore, this study examined how and why indigenous people are participating in ecotourism development by taking a case study of a village in Bukit Tigapuluh National Park, Indonesia. This study collected data through semi-structured interviews and field observations using a qualitative method. Four forms of indigenous people’s participation in ecotourism development are found in this study, including discovering tourist attractions, conserving the forest, working in the ecotourism sites, and managing ecotourism attractions. Furthermore, this study discovered two factors encouraging their participation, i.e., community empowerment by the national park office and perceived positive impacts of ecotourism.